Organic Light‐Emitting Diodes: Organic Light‐Emitting Diodes: Pushing Toward the Limits and Beyond (Adv. Mater. 35/2020). Issue 35 (1st September 2020) - Song, Jinouk; Lee, Hyeonwoo; Jeong, Eun Gyo; Choi, Kyung Cheol; Yoo, Seunghyup
Abstract : Recent advances in highly efficient organic light‐emitting diodes (OLEDs) and their emerging applications, including phototherapeutic patches, biometric sensors, and textile displays are reviewed by Kyung Cheol Choi, Seunghyup Yoo, and co‐workers in article number 1907539 . For efficiency improvement, the importance of outcoupling structures coupled with horizontally oriented dipole emitters is highlighted.